The cardiac autonomic response to acute psychological stress in type 2 diabetes - Monzer, Nelly Lou; Hartmann, Mechthild; Buckert, Magdalena; Wolff, Kira; Nawroth, Peter Paul; Kopf, Stefan; Kender, Zoltán; Friederich, Hans-Christoph; Wild, Beate (PLOS ONE, 2022)
Background Impaired cardiac autonomic control is common among people with type 2 diabetes. The autonomic nervous system and its regulatory influence on the cardiovascular system also play a key role in the physiological response to psychosocial stressors. It is unclear whether the disease-related impairment of cardiac autonomic control in people with type 2 diabetes affects the stress response. The aim of this study was therefore to examine the cardiac autonomic and the psychological stress response of people with type 2 diabetes compared to healthy control participants. Methods We used the trier social stress test to induce stress in n = 51 participants with type 2 diabetes and n = 47 healthy controls. We assessed heart rate (HR) and heart rate variability (HRV) using six ECG samples before, during and after the stress test. We measured participants’ psychological stress response using visual analogue scales. Results Longitudinal multilevel models showed an attenuated HR increase in response to the stress test combined with a slower HR recovery after the stress test, in people with type 2 diabetes. This pattern was accompanied by significantly lower low frequency HRV but no differences in high frequency HRV between the groups. Additionally, people with type 2 diabetes showed an increased level of self-reported psychological tension 45 minutes after the stress test. Conclusions The impairment of the autonomic nervous system found in people with type 2 diabetes is reflected in the HR response to stress—but not in the HRV response—and partially mirrored in the psychological stress response. Our results underline the importance of considering the interplay of psychosocial stress and disease-related changes in the physiological stress response system in research and treatment of type 2 diabetes.